The long term vaccine‐induced anti‐SARS‐CoV‐2 immune response is impaired in quantity and quality under TNFα blockade. Issue 12 (19th August 2022) - Geisen, Ulf Martin; Rose, Ruben; Neumann, Franziska; Ciripoi, Maria; Vullriede, Lena; Reid, Hayley M.; Berner, Dennis Kristopher; Bertoglio, Federico; Hoff, Paula; Hust, Michael; Longardt, Ann Carolin; Lorentz, Thomas; et al.
Abstract: The humoral immune response to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccination in patients with chronic inflammatory disease (CID) declines more rapidly with tumor necrosis factor‐α (TNF‐α) inhibition. Furthermore, the efficacy of current vaccines against Omicron variants of concern (VOC) including BA.2 is limited. Alterations within immune cell populations, changes in IgG affinity, and the ability to neutralize a pre‐VOC strain and the BA.2 virus were investigated in these at‐risk patients. Serum levels of anti‐SARS‐CoV‐2 IgG, IgG avidity, and neutralizing antibodies (NA) were determined in anti‐TNF‐α patients ( n = 10) and controls ( n = 24 healthy individuals; n = 12 patients under other disease‐modifying antirheumatic drugs, oDMARD) before and after the second and third vaccination by ELISA, immunoblot and live virus neutralization assay. SARS‐CoV‐2‐specific B‐ and T cell subsets were analysed by multicolor flow cytometry. Six months after the second vaccination, anti‐SARS‐CoV‐2 IgG levels, IgG avidity and anti‐pre‐VOC NA titres were significantly reduced in anti‐TNF‐α recipients compared to controls (healthy individuals: avidity: p ≤ 0.0001; NA: p = 0.0347; oDMARDs: avidity: p = 0.0012; NA: p = 0.0293). The number of plasma cells was increased in anti‐TNF‐α patients (Healthy individuals: p = 0.0344; oDMARDs: p = 0.0254), while the absolute number of SARS‐CoV‐2‐specific plasma cells 7 days after 2nd vaccination were comparable. Even after a third vaccination, these patients had lower anti‐BA.2 NA titres compared to both other groups. We show a reduced SARS‐CoV‐2 neutralizing capacity in patients under TNF‐α blockade. In this cohort, the plasma cell response appears to be less specific and shows stronger bystander activation. While these effects were observable after the first two vaccinations and with older VOC, the differences in responses to BA.2 were enhanced.